Practical algorithms in pediatric hematology and oncology - Sills, Richard H (Karger, 2003)
This is the only comprehensive collection of algorithms which exclusively addresses hematologic and oncologic problems affecting neonates, children and adolescents. Examining clinical problems which challenge the pediatrician, general practitioner and family practice physician, each algorithm utilizes a concise, step-by-step approach based upon clues from the history, physical examination and laboratory studies. The algorithms addressing differential diagnosis clearly distinguish between the most common etiologies, those that are less frequent, and finally some that are rare but important to recognize. The 51 topics include evaluation of anemia, sickle cell anemia, thalassemia, hemolytic anemia, the bleeding child, thrombocytopenia and other platelet disorders, hemophilia, leukocyte disorders, leukemias, lymphadenopathy, splenomegaly, approaches to mass lesions in the mediastinum, abdomen, pelvis, bones and soft tissues as well as approaches to potential emergencies such as tumor lysis.
Practical algorithms in pediatrics
Keywords: Pediatrics; hematologie a transfuzní lékařství; Hematology; pediatrie; lékařská onkologie; Medical Oncology; hematologie; onkologie